INFLUENCE OF ALUMINUM ON MINERAL NUTRIENT UPTAKE AND ACCUMULATION IN URTICA PILULIFERA L. - Özyiǧit, Ibrahim Ilker (My University, 2014)
Pollutants can have detrimental effects on living organisms. They can cause toxicity, damaging cells, tissues and organs because of their high concentrations or activities. Plants provide a useful system for screening and monitoring environmental pollutants. Among pollutants, aluminum is considered as a primary growth limiting factor for plants resulting in decreased plant growth and development. Although considered to be a non-essential and highly toxic metal ion for growth and development, aluminum (Al) is easily absorbed by plants. Urticaceae family members have high nutrient requirements demonstrated by leaves containing high levels of calcium (Ca), iron (Fe), magnesium (Mg), and nitrogen (N). Urtica pilulifera is one of the important traditional medicinal plants in Turkey. In this study, U. pilulifera was used as a bioindicator to investigate the possible differences in the absorption and accumulation of mineral nutrients at different levels of the Al exposure and examine the mineral nutrition composition of U. pilulifera under Al stress. Also, some growth parameters (leaf-stem fresh and dry weights, root dry weights, stem lengths and leaf surface area) were investigated. U. pilulifera seedlings were grown for two months in growth-room conditions and watered with spiked Hoagland solution, which contained 0, 100, and 200 μM aluminium chloride (AlCl3). It was observed that macro- and micro-nutritional status of roots and leaves was altered by Al exposure. The concentrations of some macro- and micronutrients were reduced while concentrations of others were increased by excess of Al. Some macro- and micronutrients were increased at low level of Al whereas reductions were observed at high level of Al, and vice versa. The patterns were dependent on the macro- or micronutrient and the plant part. © 2014 Copyright Taylor and Francis Group, LLC.
Keywords: aluminum (Al) toxicity; mineral nutrient accumulation; mineral nutrient uptake; Roman nettle; Urtica pilulifera